Housing Market in Metropolitan Colombo: New Trends. The Sri Lanka Journal of Humanities and Social Sciences, Colombo: National Centre for Advanced Studies (NCAS). - Niriella, N.C (My University, 2011)
The study conducted in the Colombo Metropolitan Region, addresses to the emerging nexus between public and private sectors in urban housing, and market forces. The commercialization of private sector build housing has been on the increase builders in the market, where the state has incurred to its dwindling resources and infra-structure. The study reveals that the rising demand especially among middle and upper income groups for apartments in private housing schemes, along with multiple amenities. This has resulted in a steep rise in land prices. Also private housing is mainly tapping the middle and upper middle classes, but not the lower middle and the poor. These categories in the housing market are mainly served through the state funded subsidized housing schemes. Further, the researcher has shown how the banking facilities for housing loans have further enhanced the interest of people in private housing, creating a big boost to the housing market. The whole process has led to the emergence of urban social classes very distinct from one another and drawing an identity from the housing structures.